Evaluation of the Occlusal Relationship between Deciduous Teeth in Breastfed Children and Bottle-Fed Children - Haleh Hali; Anahita Ghorbani; Abolfazl Hosseinnataj; Reza Motebassem; Melika Mollaei (Mashhad University of Medical Sciences, 2023)
Background: One of the factors affecting deciduous occlusion is infant feeding modes. The objective of this research was to identify and document the malocclusions that arise due to various approaches of infant feeding, and to assist in clarifying ambiguities surrounding skeletal growth complications that result from infant feeding practices.Materials and Methods: This cross-sectional descriptive-analytical study was conducted in 2021 on 284 children with an age range of 4-5 years who were selected from kindergartens and preschools in Sari by cluster sampling and then systematic sampling. After obtaining written consent from the parents and recording the child's personal information in the demographic checklist, the surface of the teeth was cleaned with a sterile gauze and then examined. The relationship of deciduous molars, overjet and overbite, open bite, posterior crossbite, and the relationship of deciduous canines were recorded. Data analysis was performed by Chi-square and one-way ANOVA using SPSS software (version 22). P-values of <0.05 were considered statistically significant. Results: Infant feeding showed a significant relationship with the mother's education level, as well as the parents' occupational status. However, feeding type showed no significant relationship with the child's gender, number of children in the family, age of the child, age of the parents, and duration of milk feeding. Mesial step and distal step patterns were significantly more frequent in deciduous molars of breastfed children and those fed with formula milk, respectively (P<0.001). Furthermore, the type of feeding was not significantly associated with overjet, overbite, posterior crossbite, and deciduous canine relationship.Conclusion: Breastfeeding is regarded as the most complete method of feeding infants, which is also a predisposing factor for developing a mesial step deciduous dentition.